Successful live birth after heterotopic ruptured cornual pregnancy with twin intrauterine gestation in an in vitro fertilization conception - Bansal, Venus; Chhabra, Muskaan; Chopra, Rahul; Prajapati, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Heterotopic pregnancies, especially in the cornual region which were a rarity till recent times, have become a more common occurrence due to increasing practice of assisted reproduction. Optimal management of such cases is imperative to manage the risk of hypotension and shock in case of rupture and to judiciously preserve the intrauterine pregnancy. Here we are reporting a case of IVF conception of twin intrauterine pregnancy with a cornual heterotopic pregnancy. Patient presented to the emergency department with features of acute abdomen, haemoperitoneum and shock. Ultrasound findings were suggestive of rupture of cornual heterotopic pregnancy, 1500 ml haemoperitoneum with live twin intrauterine gestation. Patient was resuscitated with iv fluids blood transfusion. Immediate laparotomy was done and cornual site repaired and covered with an omental patch while preserving the intrauterine gestations. Thereafter, pregnancy was carefully monitored with a high index of suspicion for rupture of site of cornual repair with advancing gestational age. Patient was readmitted at 24 weeks with pain abdomen and cornual site was found to be 4mm in thickness. She was managed conservatively till 27 weeks when she had preterm rupture of membranes and emergency LSCS was done. She delivered healthy twin male babies, 780 gmb and 795 gm respectively. This case demonstrates that cornual heterotopic pregnancy is a diagnosis which may be easily missed and can present as a life-threatening complication if it ruptures and significant intraperitoneal bleeding occurs. However, it is possible to successfully manage these cases with timely intervention, proper uterine reconstruction and monitoring of intrauterine gestation.